Silicon-Containing Dendritic Polymers - Dvornic, Petar R. (Springer, 2017)
This is the first book of its kind to solely focus on silicon containing dendritic polymers. The contributions of those experts who either originally introduced each field or who played a major role in its progress are reported. The developments in each of the major areas of this field are presented from their origins to the present. Each chapter is held to the highest scientific standards. Hence, it is anticipated that this text will become an invaluable guide and vanguard of reference for experienced scientists interested in the fields of polymer and material science, synthetic chemistry, and nanotechnology. It will also serve advanced graduate students either as a source of creative inspiration or as a textbook for appropriate courses.